Fructose Uptake in Sinorhizobium meliloti Is Mediated by a High-Affinity ATP-Binding Cassette Transport System - Lambert, Annie (American Society for Microbiology, 2001)
By transposon mutagenesis, we have isolated a mutant of Sinorhizobium meliloti which is totally unable to grow on fructose as sole carbon source as a consequence of its inability to transport this sugar. The cloning and sequencing analysis of the chromosomal DNA region flanking the TnphoA insertion revealed the presence of six open reading frames (ORFs) organized in two loci, frcRS and frcBCAK, transcribed divergently. The frcBCA genes encode the characteristic components of an ATP-binding cassette transporter (FrcB, a periplasmic substrate binding protein, FrcC, an integral membrane permease, and FrcA, an ATP-binding cytoplasmic protein), which is the unique high-affinity (K(m) of 6 μM) fructose uptake system in S. meliloti. The FrcK protein shows homology with some kinases, while FrcR is probably a transcriptional regulator of the repressor-ORF-kinase family. The expression of S. meliloti frcBCAK in Escherichia coli, which transports fructose only via the phosphotransferase system, resulted in the detection of a periplasmic fructose binding activity, demonstrating that FrcB is the binding protein of the Frc transporter. The analysis of substrate specificities revealed that the Frc system is also a high-affinity transporter for ribose and mannose, which are both fructose competitors for the binding to the periplasmic FrcB protein. However, the Frc mutant was still able to grow on these sugars as sole carbon source, demonstrating the presence of at least one other uptake system for mannose and ribose in S. meliloti. The expression of the frcBC genes as determined by measurements of alkaline phosphatase activity was shown to be induced by mannitol and fructose, but not by mannose, ribose, glucose, or succinate, suggesting that the Frc system is primarily targeted towards fructose. Neither Nod nor Fix phenotypes were impared in the TnphoA mutant, demonstrating that fructose uptake is not essential for nodulation and nitrogen fixation, although FrcB protein is expressed in bacteroids isolated from alfalfa nodulated by S. meliloti wild-type strains.